Successful retrieval of migrated Amplatzer septal occluder - Shirodkar Salil; Patil Sushant; Pinto Robin; Dalvi Bharat (Wolters Kluwer Medknow Publications, 2010)
Migration and embolization of the Amplatzer septal occluder (ASO) have been reported. However, there is only limited information on the methods of systematic retrieval of these devices. In this report, we describe the a case of a 4 year old girl who underwent closure of her atrial septal defect (ASD) using a 17 mm ASO. The device migrated in to the right atrium an anteroposterior plane 24 hours later with a resultant residual shunt. The device was successfully retrieved percutaneously and the ASD was closed using a 20 mm ASO.